(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Terminology is not just a technical or specific example of common language. In today’s society, which values science and technology, the way expert knowledge concepts are named, structured, described and translated has given the term or naming of knowledge concepts. Get the expert up on stage. Information in scientific and technical texts is encoded in specialized terms or knowledge units, which are points of access to more complex knowledge structures. Beneath the information contained in the text are entire conceptual domains, explicitly and implicitly presented, and representing codified expertise. To produce a specialized text, translators and technical writers must have excellent linguistic proficiency in the area of concept, content, and understanding of the recipient or recipient of the text. To translate a text into a specialized language, the translator must go beyond correspondence at the level of individual terms and be able to establish multilingual references to the entire knowledge structure. Only then can they reach the level of understanding necessary to produce an equivalent text in the target language.